UTILIZAÇÃO DE MODELOS DIDÁTICOS TATEÁVEIS COMO METODOLOGIA PARA O ENSINO DE BIOLOGIA CELULAR EM TURMAS INCLUSIVAS COM DEFICIENTES VISUAIS (Revista Contexto & Educação, 2019)
The understanding of cellular structures, due it microscopic nature, requires a high level of abstraction, and it becomes a challenge for students with and without visual limitation. Alternative methodologies can enable students to visualize, manipulate and touch on models that represent real cell structures, and thus improve the learning. In this study, we tested the hypothesis that three-dimensional models of several cell types, as well as the process involving cells (cell multiplication and healing), initially tactilely used, can be an efficient tool for the teaching of Cell Biology in a perspective of inclusion of pupils visually impaired.  Participated of study  23 seers and 5 visually impaired students, 8 and 9 years of elementary school, from two public schools in Rio Grande do Sul- Brazil. The results showed that the use of three-dimensional didactic models, constructed in such a way as to be able to manipulate them, can contribute to the inclusion of students with visual impairment in the regular classroom, as well as make the teaching of cellular biology more attractive and dynamic. Seer students first and have made good use of learning about the diversity of cell forms and the role of cells in growth and healing processes.
Keywords: Visual Deficiency; Didactic Models; Cell; Inclusion